Techniques in wildfowl taxonomy - Matthews, G V T (Wildfowl, 1959)
A better understanding of the taxonomy of the Anatidae--the evolutionary relationships within the Family and its position with regards to other groups of birds--has from the start been one of the main aims of our research programme. The unique comparative Collection of wildfowl at Slimbridge, in which five-sixths of the living species have been represented at some time, offers outstanding opportunities for such work. Their study has gone forward both by work carried out at Slimbridge and by the provision of material for workers in other institutes. Many and diverse methods have been used and here an attempt is made to draw the threads together and indicate the scope of present researches, without reporting on the results in detail. It is intended that this should be done in a later paper.